Evaluating the potential of effluent extracts from pulp and paper mills in Canada, Brazil, and New Zealand to affect fish reproduction: Estrogenic effects in fish. (27th December 2016) - Orrego, Rodrigo; Milestone, Craig B.; Hewitt, L. Mark; Guchardi, John; Heid‐Furley, Tatiana; Slade, Alison; MacLatchy, Deborah L.; Holdway, Douglas
Abstract: The authors examined the potential of pulp mill effluent from pulp‐producing countries (Canada, Brazil, New Zealand) to affect fish reproduction. Specifically, the estrogenic effects in juvenile rainbow trout ( Oncorhynchus mykiss ) pulse‐exposed to 11 different mill effluent extracts (intraperitoneal injections of solid‐phase extraction–dichloromethane nonpolar fraction). The results indicated that effluent extracts were estrogenic in juvenile trout irrespective of the gender, as reflected by increasing level of plasma vitellogenin (VTG; Brazil > New Zealand > Canada). Despite the high variability observed among mills, differences in VTG levels were related to the type of mill process (kraft > elementary chlorine‐free kraft > thermomechanical pulping). Moreover, effluent treatments did not appear to significantly decrease VTG induction. A consistent estrogenic effect was observed in those mills that process a combination of feedstocks (softwood and hardwood), with the highest increase in VTG related to eucalyptus feedstock. The results demonstrate significant estrogenic effects of pulp mill effluents on chronically exposed juvenile trout, suggesting that in vivo metabolic activation of precursors is necessary to cause the observed increases in VTG levels. This molecular estrogenic response provides a useful starting point for predicting population‐level impacts through the adverse outcome pathway methodology. Environ Toxicol Chem 2017;36:1547–1555. © 2016 SETAC